Use of Artificial Intelligence in IT Audit: A case study on professional services firm - Salonen, Jami (My University, 2024)
Artificial intelligence applications have advanced significantly in recent years. Although AI is not a new phenomenon, recent developments in large language model applications have brought AI into our everyday lives. One of the well-known examples is ChatGPT, developed by OpenAI, which is a chat-based large language model accessible not only to technologically advanced individuals but also to everyday users. Many large professional firms have announced significant investments in artificial intelligence technologies and tools. The purpose of an information technology audit is to evaluate the risks associated with the IT environment. The need for IT audits arises from a variety of laws and regulations. As IT systems become more interconnected and complex, they become more difficult to comprehend and maintain. According to the literature is spending on cloud services also on the rise. Previous research suggests that integrating AI into audit processes could enhance quality. However, there are numerous concerns regarding the use of AI in different tasks, including issues of accountability, transparency, and privacy. This study is based on existing literature on information technology audit and artificial intelligence. It is a qualitative case study that seeks to examine the impact of AI tools on IT audit processes through interviews and thorough analysis. The interviewees included experienced professionals from the auditing industry. The findings suggest that AI tools have the potential to streamline manual processes, particularly in resource-intensive tasks. While many benefits are anticipated, audit professionals have a cautious approach to AI integration. However, regulation is not seen to essentially hinder AI adoption. Professionals urge human oversight when utilizing AI tools in audit processes.

Tekoälysovellukset ovat kehittyneet merkittävästi viime vuosina. Vaikka tekoäly ei ole uusi ilmiö, viimeaikaiset kehitysaskeleet suuriin kielimalleihin perustuvissa sovellutuksissa ovat tuoneet tekoälyn osaksi jokapäiväistä elämäämme. Yksi tunnetuista esimerkeistä on OpenAI:n kehittämä ChatGPT, joka on keskustelupohjainen suuri kielimalli. Keskustelupohjainen kielimalli on käytettävissä paitsi teknisesti edistyneille henkilöille niin myös tavallisille käyttäjille. Monet suuret asiantuntijayritykset ovat uutisoineet merkittävistä investoinneista tekoälyteknologioihin ja -työkaluihin. IT-tarkastuksen tarkoituksena on arvioida IT-ympäristöön liittyviä riskejä. IT-tarkastusten tarve johtuu lainsäädännöstä ja regulaatiosta. Kun IT-järjestelmät muuttuvat yhä enemmän toisiinsa kytketyiksi ja monimutkaisemmiksi, tulevat ne vaikeammiksi ymmärtää ja ylläpitää. Kirjallisuuden perusteella myös pilvipalveluihin käytettävät menot ovat kasvussa. Aiempi tutkimus viittaa siihen, että tekoälyn hyödyntäminen auditointiprosesseissa voisi parantaa tarkastuksen laatua. Kuitenkin tekoälyn hyödyntämisessä eri käyttötapauksissa on lukuisia huolenaiheita, kuten vastuunkantoon, läpinäkyvyyteen ja yksityisyyteen liittyvät kysymykset. Tämä tutkimus perustuu olemassa olevaan kirjallisuuteen IT-tarkastuksesta ja tekoälystä. Tämä on laadullinen tapaustutkimus, joka pyrkii selvittämään tekoälytyökalujen vaikutusta IT-tarkastukseen haastattelujen ja niiden analysoinnin avulla. Haastateltavat olivat kokeneita ammattilaisia tarkastusalalta. Tulokset viittaavat siihen, että tekoälytyökalut voivat tehostaa manuaalisia prosesseja ja resursseja vaativia tehtäviä. Vaikka tekoälyn integroinnin odotetaan tuovan monia etuja, tarkastusalan ammattilaiset suhtautuvat siihen varovaisesti. Sääntelyä ei kuitenkaan nähdä olennaisena esteenä tekoälyn käyttöönotolle. Ammattilaiset korostavat ihmisen valvonnan tarvetta käytettäessä tekoälytyökaluja auditointiprosesseissa.
Keywords: information technology audit, IT audit, artificial intelligence, large language model, tietojärjestelmätarkastus, IT-tarkastus, IT-auditointi, tekoäly, AI, suuri kielimalli